2002
DOI: 10.1038/sj.jea.7500225
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mouthing behavior in young children

Abstract: Young children may be more likely than adults to be exposed to pesticides following a residential application as a result of hand -and object -to -mouth contacts in contaminated areas. However, relatively few studies have specifically evaluated mouthing behavior in children less than 5 years of age. Previously unpublished data collected by the Fred Hutchinson Cancer Research Center ( FHCRC ) were analyzed to assess the mouthing behavior of 72 children ( 37 males / 35 females ). Total mouthing behavior data inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 13 publications
11
117
0
1
Order By: Relevance
“…Freeman et al (2001) observed children aged 3-12 years and also report a difference in object-to-mouth but not hand-to-mouth contact frequency in children o5 years compared with those Z5 years. In other studies, significant differences in mouthing frequency have been reported between infants and toddlers (Beamer et al, 2008), children o and Z2 years of age (Tulve et al, 2002;AuYeung et al, 2004) and among children o6 years of age . Our study is the first to specifically document that mouthing behavior does not decrease with age among 7-12-year olds.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Freeman et al (2001) observed children aged 3-12 years and also report a difference in object-to-mouth but not hand-to-mouth contact frequency in children o5 years compared with those Z5 years. In other studies, significant differences in mouthing frequency have been reported between infants and toddlers (Beamer et al, 2008), children o and Z2 years of age (Tulve et al, 2002;AuYeung et al, 2004) and among children o6 years of age . Our study is the first to specifically document that mouthing behavior does not decrease with age among 7-12-year olds.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have quantified these mouthing and hand contact behaviors in children (Zartarian et al, 1997aBrinkman et al, 1999;Reed et al, 1999;Freeman et al, 2001Freeman et al, , 2005Tulve et al, 2002;AuYeung et al, 2004;Black et al, 2005;Auyeung et al, 2006;Beamer et al, 2008); however, we know of only one other study that has reported any data on children over 6 years of age (Freeman et al, 2001). Meta-analyses of the data collected from younger children have indicated that mouthing decreases with age and other studies have reported differences by age in the frequency, with which children contact different types of objects or fomites with their hands (Freeman et al, 2001;Auyeung et al, 2006;Beamer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2,69,75 According to the literature, children in general ingest about 50 mg/day house dust during the summer and 100 mg/day during the winter, when they spend more time indoors. 57,58 In the case of pica behavior (eating of non-nutritive substances), uptake can reach up to 2--30 g/day.…”
Section: Resultsmentioning
confidence: 99%
“…Observations may be conducted by a parent, after receiving special instructions, or by a trained observer (Tulve et al, 2002). Videotaping to record children's behavior is done by a trained technician.…”
Section: Introductionmentioning
confidence: 99%